2013
DOI: 10.5433/2316-5200.2013v2n3espp21
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da cisteína adicionada ao meio diluente sobre a cinética de espermatozóides ovinos após descongelamento

Abstract: RESUMOAmostras seminais de carneiros sexualmente maduros foram misturadas em forma de pool, diluídas em alíquotas contendo diferentes concentrações de cisteína (0, 2.5 mM; 5.0 mM; 7.5 mM) e submetidas ao protocolo automatizado de congelamento. Após o descongelamento as amostras foram avaliadas quanto à cinética espermática utilizando o sistema Computer Assisted Sperm Analysis (CASA). Os resultados mostraram elevação nas tres variáveis diretamente relacionadas à habilidade do espermatozóide em alcançar o local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…In their study on pig sperm, Broekhuijse et al (2012) demonstrated that progressive motility, VCL, and BCF are related to the frequency of deliveries; and that the total motility, VAP, VSL, and ALH affected slightly but significantly (P < 0.05) the number of piglets born. In sheep, the kinetic variables VAP, VCL, and VSL have been associated with the increased ability of sperm to reach the fertilization site and fertilize the egg (CORANDIN et al, 2013). However, since no well-defined cause and effect trend was observed between the composition of the diluting extenders and between the preservation methods with the kinetic attributes in this experiment, we cannot infer whether diluting extenders with LDL would result in a higher or lower fertilization probability.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…In their study on pig sperm, Broekhuijse et al (2012) demonstrated that progressive motility, VCL, and BCF are related to the frequency of deliveries; and that the total motility, VAP, VSL, and ALH affected slightly but significantly (P < 0.05) the number of piglets born. In sheep, the kinetic variables VAP, VCL, and VSL have been associated with the increased ability of sperm to reach the fertilization site and fertilize the egg (CORANDIN et al, 2013). However, since no well-defined cause and effect trend was observed between the composition of the diluting extenders and between the preservation methods with the kinetic attributes in this experiment, we cannot infer whether diluting extenders with LDL would result in a higher or lower fertilization probability.…”
Section: Discussionmentioning
confidence: 38%
“…Furthermore, the reduction in the activity of these two enzymes was higher using an egg yolk-based diluting extender than in extenders with LDL. Corandin et al (2013) showed that diluting extenders with LDL instead of whole egg yolk reduced the negative effects caused by the cooling and freezing processes on the activity of the antioxidant enzymes from ram spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Zootec., v.70, n.5, p.1547-1556, 2018 For the parameters curvilinear velocity (CLV) and straightness (STR), the results found in this study were higher than the 173.4±4.33 and 77.1±1.56, respectively, published by Sicherle (2007), who added catalase to the extender, and similar when the author added trolox (179.2 ± 5.98 and 80.5±1.29). Regarding average path velocity (APV), amplitude of lateral head displacement (ALH), and straight-line velocity (SLV), the results of this study were also superior to those found by Corandin et al (2013), who added 2.5mM cysteine to the extender. However, the linearity of the sperm diluted in extender with aqueous extract of noni was lower than that of the afore-mentioned studies.…”
Section: Discussioncontrasting
confidence: 60%